Clonidine for pain-related distress in Aboriginal children on a penicillin regimen to prevent recurrence of rheumatic fever - Alice Mitchell; John Kelly; Jeff Cook; Natalie Atkinson; Brian Spain; Bo Remenyi; Vicki Wade; Anna Ralph (James Cook University, 2020)
Context: Indigenous children and adolescents in Australia and globally bear the burden of acute rheumatic fever (ARF). It has been virtually eliminated in well-resourced, developed settings. ARF is an autoimmune response to infection with group A Streptococcus. The mainstay of management is long-acting intramuscular penicillin injections to prevent recurrence of ARF and development of rheumatic heart disease (RHD), comprising valvular pathology and attendant complications. In Australia, penicillin injections are currently prescribed every 28 days for 5-10 years after diagnosis of ARF, depending on cardiac involvement. Adherence to this regimen reduces ARF recurrences and RHD progression. 'Days at risk' of ARF recurrence are calculated as the number of days after day 28 that an injection is not received. Adherence to the injection schedule has been reported as difficult in most global locations due to the painful nature of the injections, the long timeframes of the prescription, young age of patients, access problems and costs in some locations. The newly updated Australian guideline on the prevention, diagnosis and management of ARF and RHD has a chapter dedicated to secondary prophylaxis. This chapter takes into account cultural considerations and advises on ways to minimise pain and distress of injections in children such as pain gate strategies, distraction techniques and concurrent injection of local anaesthetic. Issues: Some children continue to find the injection regimen traumatising despite strategies to reduce pain and fear. Clinicians providing the injections to children also find the injecting episodes distressing if pain is not effectively minimised. An Aboriginal Community Controlled Health Service in a remote setting in northern Australia addressed the issue of severe trauma of injection episodes experienced by an Aboriginal boy aged 7 years. Usual strategies were not effective, so advice was sought from an expert anaesthetist at a tertiary hospital. As a result, oral clonidine 3 µg/kg was trialled 45 minutes prior to the penicillin injection. Procedural coaching and monitoring protocols specific to administration of clonidine in children under their care were created by the health service. The initial dose of clonidine was delivered with the child as an inpatient. Lessons learned: Clonidine was successful in reducing pain related distress and facilitating adherence to the penicillin regimen. Subsequent doses were delivered and monitored in a remote setting by nurses. After 18 months, the boy no longer required clonidine due to his increased coping capacity. A second child was recognised with similar trauma and has been taking clonidine for pre-procedural sedation for 6 months with good effect and no adverse effects. An additional child was similarly prescribed clonidine without success. Failure in that instance was attributed to lack of procedural coaching and receiving the initial dose of clonidine in an emergency department in hurried circumstances. Individualised child-focused and culturally appropriate care in remote settings is feasible: in this instance team planning for use of clonidine and procedural coaching when other measures have failed. However, for children with RHD, or other comorbidities, advice from the child's treating cardiologist is required prior to prescribing clonidine due to possible adverse consequences. These include hypotension and atrioventricular block, which could lead to haemodynamic compromise in the setting of moderate to severe RHD.